Mosaic Fleur-de-Profunda Artery Perforator Flap for Autologous Breast Reconstruction. Issue 3 (March 2019) - Bourn, Lynn; Torabi, Radbeh; Stalder, Mark W.; St. Hilaire, Hugo; Allen, Robert J.; Delatte, Stephen J.; Matatov, Tim S.; Torabi, Rozbeh; Zakhary, Joseph; Tessler, Oren
Abstract : Summary: Perforator-free flaps, in autologous breast reconstruction, have expanded to exploit tissue available at smaller donor sites while retaining high success and low risk rates. Abdominal based flaps, such as the deep inferior epigastric perforator, remain the most common; however, when the abdomen is not an appropriate donor site, lower extremity flaps are options. The profunda artery perforator has the benefit of hiding unsightly scar in the gluteal crease but has the drawback of poor donor site volume. Our mosaic fleur-de-profunda artery perforator flap technique for breast reconstruction has shown to increase volume with the addition of a vertical limb, include full angiosome of perforators, and exhibit donor site morbidity equivalent to a medial thigh lift.